Giant cell reparative granuloma of the nasal cavity: a rare site of presentation with review of literature - Satya Dutta; Pakesh Baishya; Vandana Raphael; Biswajit Dey; Jaya Mishra (University of São Paulo, 2021)
Giant cell reparative granuloma (GCRG) was first described in the 1950s. It is an uncommon and benign reactive tumor that is believed to occur after trauma or inflammation. It most commonly occurs in the maxilla and mandible and rarely affects the nasal cavity. It is often seen in children and during the second to third decades of life, predominantly seen among females. Histopathologically, GCRG shows many osteoclast-like multinucleated giant cells scattered in a background of mononuclear stromal cells and spindle-shaped fibroblasts also associated with areas of hemorrhage. The distinction between GCRG and giant cell tumors (GCT)is crucial since both have a similar clinical and histological presentation, but both have different management. GCTs have malignant potential, may metastasize, and have a high rate of recurrence. Surgical excision is the mainstay therapy of GCRG to ensure a low rate of recurrence. Here we discuss two cases GCRG, both presenting as nasal mass.